Textured PbI2 photocathodes obtained by gas phase anion replacement. (10th November 2017) - Tiwari, Devendra; Fermin, David J
Abstract: High quality PbI2 films are prepared by a new route based on iodination of solution processed PbS films at room temperature. The PbI2 films are characterized by a highly textured morphology with flake-like particles sizing 500 and 800 nm across. Quantitative X-ray diffraction and resonance Raman spectroscopy demonstrate the crystallization of highly phase pure 2H-PbI2 with lattice parameters: a = 4.5505(9) Å, c = 6.9784(14) Å. Electronic structures and vibrational modes are calculated employing DFT. Transmittance and reflectance measurements are characterized by a sharp absorption edge corresponding to a direct band gap transition of 2.41 eV. Photoelectrochemical measurements carried out in 0.1 M KI solution showed that the material behaves as a p-type semiconductor with an apparent donor concentration of the order of 10 15  cm −3 as well as stable photoresponses associated with hydrogen evolution with nearly 50% incident photon-to-current efficiency. Quantitative analysis of the spectral and potential dependence of the photocurrent responses shows that surface recombination is negligible even at the flat band potential. We conclude that I − species stabilizes the semiconductor surface, generating an ideal semiconductor/electrolyte junction, while enabling the transfer of minority carrier from the conduction band edge dominated by lead antibonding p-orbitals